Assessment of risk factors and identification of potential biomarkers associated with breast cancer-related lymphedema in Malaysian breast cancer survivors - Md Yusof, Khairunnisa' (2022)
Survival rates for breast cancer have been increasing over the years due to early detection and improved treatment. However, these cancer survivors faced several challenges following cancer treatment including breast cancer-related lymphedema (BCRL). BCRL is characterized by fluid retention and abnormal swelling in one or both arms that arises after obstruction of lymphatic vessels resulting from surgery insults or radiotherapy. The aim of this study was to identify risk factors and potential biomarkers associated with BCRL in the Malaysian breast cancer population. A set of questionnaires comprising demographic and medical history, quality of life assessment, and upper quadrant function were self-administered by 173 female breast cancer survivors. Anthropometry, arm circumference measurement, and ultrasound examination of the arms were performed on all participants before they were divided into either (1) lymphedema group (BCRL), based on self-reporting diagnosis and arm circumference difference of ≥1.5cm between the affected and unaffected arms or the (2) non-lymphedema group (non-BCRL). For laboratory analysis, a total of 6mL of whole blood was collected and processed to obtain the serum. Experimental analysis including small RNA-sequencing, quantitative polymerase chain reaction (qPCR), and detection of adipokines levels was performed on all serum samples. One hundred and sixty women were eligible for the study and 33 of them (20.5%) were classified into the lymphedema group. Those with multiple breast cancer surgeries on the same site of the breast, had ≥10 lymph nodes excised, higher body mass index (≥25 kg/m2), higher waist-to-hip ratio (>0.9), hypertension, and received fewer rehabilitation treatment (<2 types of treatment) were associated with increased odds of lymphedema by two to five-fold. Diabetes mellitus was found to have a significant association with the development of early-onset lymphedema within the lymphedema group (p<0.05). The analysis of arm circumference difference revealed the highest difference in the forearm when compared to the other measured sites. Analysis of the ultrasound images of lymphedema patients showed skin and subcutaneous thickness of the forearm were higher in the affected arms accompanied by accumulation of fat with a lattice-like structure when compared to the unaffected arms. MicroRNA profiling results demonstrated that miR-199a-3p and miR-151a-3p were downregulated in the early-onset lymphedema group when compared to the late-onset and non-lymphedema group (p<0.05). Findings from the pathway analysis showed the involvement of metabolic syndrome (MetS) pathways including sphingolipid, phospholipase D, adrenergic signalling in cardiomyocytes and cGMP-PKG signalling in the lymphedema group. One of the analysed adipokines, leptin concentration was significantly higher in the lymphedema group and correlated with BMI, fat percentage, and hypertension. The adiponectin/leptin ratio was lower in the lymphedema group (p<0.05) and negatively correlated with blood pressure and waist-to-hip ratio (p<0.05). Taken together, findings between the modifiable and molecular factors in the present study revealed a strong association between BCRL with MetS in the study population. This study has characterised risk factors and potential biomarkers of BCRL and this has provided a better understanding of the condition that may lead to the development of a screening tool and molecular-based therapies for lymphedema.